(untitled) (Marketing Journal, 2026)
Abstract This article comprehensively examines the mechanisms of wholesale trade turnover formation and the problems hindering its growth. The role of wholesale trade in the economy, its function in balancing supply and demand, and its intermediary role between producers and consumers are theoretically substantiated. The study analyzes the key performance indicators of wholesale enterprises, the efficiency of working capital utilization, the turnover ratio and turnover period of working capital, the level of inventory turnover, and the average daily trade volume. Based on the results of the analysis, scientifically grounded proposals and recommendations aimed at increasing wholesale trade turnover have been developed. Keywords: wholesale trade turnover, inventory, logistics costs, transportation costs, warehousing costs, packaging and loading expenses, ratio of trade turnover to average working capital, average daily wholesale turnover, service processes at strategic and operational levels.